EFFICIENCY OF FUNGICIDE IN THE CULTURE OF MAIZE SECOND SAFRA (Colloquium Agrariae. ISSN: 1809-8215, 2019)
One of the limitations of the expression of the productive potential of maize hybrids is the occurrence of foliar diseases in the crop. The adjustment of the time of application of the fungicides is essential to have success in controlling the main diseases, and consequently, the damages caused by them. Thus, this work had the objective of evaluating the effect of the fungicide application, at different stages of development of maize second safra. For that, two experiments were carried out in the city of Astorga-PR, in a complete block design with randomized treatments, with five replications. The evaluated treatments were composed by four fungicide (Trifloxistrobina 100 g L-1 + Tebuconazol 200 g L-1) application times: V8, Pre-Flowering, V8 + Pre-Flowering, in addition to the control. The fungicide applications reduced the severity of second crop corn diseases in Pre-Flowering and V8 + Pre-Flowering. The highest grain yield was obtained by the applications of fungicide in V8 + Pre-Flowering.